HUMAN RESOURCES MANAGEMENT IN QUR’AN’S PERSPECTIVE - Ibrahim, Farid Wajdi (UIN Ar-Raniry, 2017)
Human resource (spirit and body, aql, heart, and soul) Ã‚Â which is granted by Allah has a very powerful force as through it human is able to manage the existence resources of the universe. Principally, the entire creations of Allah are for the sake of human. Therefore, the resources must be managed properly through education in accordance with the mandate given by Allah as it is stated in Sura al Ã¢â‚¬ËœAlaq: 1-5. Ã‚Â The enrichment of human resource quality is an obligation in Islam to optimize the existing resource. Allah and His Messenger Muhammad (peace be unto him) order human to pursue the knowledge unlimitedly to find the power of Allah. Thus, all resources are bestowed by Allah must be used solely to seek His pleasure. To reach, educational institutions, teaching-learning place, play a great role, and must be well managed and planned in order to produce qualified students with good character in conformity with the teachings of the QurÃ¢â‚¬â„¢an and Hadith.